Trick or treat? Pollinator attraction in Vanilla pompona (Orchidaceae) - Watteyn, Charlotte (2021)
Natural pollination of Vanilla species remains poorly understood. Our research aimed at better understanding the pollinator attraction mechanism of the Neotropical species Vanilla pompona. Based on our results, we hypothesize that the identified pollinator Eulaema cingulata is attracted via a dual mechanism combining floral fragrance rewards and food deception.